Akceptacja oprogramowania otwartego w polskich organizacjach - Przechlewski, Tomasz; Strzała, Krystyna (Open source software adoption in Polish organizations, 2006)
Based on the well-known technology-organization-environment framework of IT adoption, a simple model was developed and evaluated empirically, using data form 216 Polish enterprises and public institutions. Statistical analysis was performed with Partial Least Squares (PLS). It was found that of the four factors considered to determine adoption decisions (benefits, costs, environment and organization) only perceived benefits and environmental impact are significant.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 142-151